2008
DOI: 10.1091/mbc.e07-06-0600
|View full text |Cite
|
Sign up to set email alerts
|

A Lipid-mediated Quality Control Process in the Golgi Apparatus in Yeast

Abstract: When heme biosynthesis is disrupted, the yeast Saccharomyces cerevisiae becomes unable to synthesize its major sterol, ergosterol, and desaturate fatty acids. We took advantage of this physiological peculiarity to evaluate the consequences of ergosterol and/or unsaturated fatty acid (UFA) depletions on the biogenesis of a model polytopic plasma membrane protein, the uracil permease Fur4p. We show that under UFA shortage, which results in low amounts of diunsaturated phospholipid species, and under ergosterol d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(66 citation statements)
references
References 61 publications
(95 reference statements)
8
58
0
Order By: Relevance
“…The intracellular trafficking of all MCC-specific transporters recognized so far depends on ergosterol biosynthesis [9,17,24,32]. For Can1, in addition, the phosphatidyl ethanolamine was shown to be required for correct delivery of the permease to the plasma membrane [23].…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…The intracellular trafficking of all MCC-specific transporters recognized so far depends on ergosterol biosynthesis [9,17,24,32]. For Can1, in addition, the phosphatidyl ethanolamine was shown to be required for correct delivery of the permease to the plasma membrane [23].…”
Section: Role Of Lipidsmentioning
confidence: 99%
“…3D). Given that a 40% saturation ratio is enough to preclude yeast cell growth (Pineau et al, 2008), we conclude from these experiments that, in contrast to OLPA, the effects of OAG on alleviating SFA lipointoxication cannot be accounted for by a simple restoration of the phospholipid content. However, the enrichment of 34:1 lipid species revealed that some of the OAG Ole chains are hydrolyzed and redistributed within phospholipids to form monounsaturated (one double bond) species Figs S2A and S3).…”
Section: Resultsmentioning
confidence: 83%
“…When grown in the absence of δ-ALA, this strain fails to synthesize heme, the prosthetic group of Ole1p, the fatty acid desaturase. As a consequence, the hem1Δ cells stop growing as early as 5 h after a shift to non-δ-ALA supplemented medium [YPD+ergosterol (Erg), denoted Ø] and this arrest correlates with an accumulation of SFA [mainly myristic (C14:0), palmitic (C16:0) and stearic (C18:0) acids] at the expense of unsaturated fatty acids [UFAs; palmitoleic (C16:1) and oleic (C18:1) acids] (Ferreira et al, 2004;Pineau et al, 2008). Interestingly, cell growth can be fully recovered and all the trademarks of SFA lipointoxication alleviated if selective UFAs, such as the mono-unsaturated fatty acid oleic acid (Ole), are added to the medium [ (Deguil et al, 2011); Table S1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have measured 30 different cells from 6 independent batches of culture and none of the hem1D yeasts showed the "Raman spectroscopic signature of life" at 1602 cm À1 . The strain also displays growth arrest at early stage so that its OD 600 never reaches the same level as wild type strains or hem1D strain supplied with ALA (data not shown, refer to [11]). This result is consistent with our expectation that the 1602 cm À1 signal is closely related to haem function.…”
Section: Resultsmentioning
confidence: 92%
“…The image and Raman spectra of wild type and hem1D yeasts compared with squalene vided with d-aminolevulinate (ALA), the product of ALA synthase, or both ergosterol and unsaturated fatty acids [11]. Therefore, it is clear that hem1D yeasts are truly deficient in haem biosynthesis and no other metabolic pathways could compensate for it.…”
Section: Introductionmentioning
confidence: 99%